Redeeming the dial : radio, religion & popular culture in America - Hangen, Tona J. (University of North Carolina Press, 2002)
Blending cultural, religious and media history, Tona Hangen offers a detailed look into the world of religious radio. She uses recordings, sermons, fan mail and other sources to tell the stories of the determined broadcasters and devoted listeners.